Arsenic Exposure, Assessment, Toxicity, Diagnosis, and Management: Guidance for Occupational and Environmental Physicians. Issue 12 (December 2018) - Baker, Beth A.; Cassano, Victoria A.; Murray, Carolyn
Abstract : N/A: Arsenic is ubiquitous in the environment and human exposure can occur from multiple possible routes including diet. Occupational medicine physicians asked to evaluate workers with elevated urine arsenic levels may be unaware that many sources of arsenic exposure are not work related. In this paper, we address arsenic exposure sources and pathways, adverse health effects of arsenic exposure and those subpopulations at increased risk, and the evaluation and treatment of those exposed to elevated arsenic levels.